Endovascular Treatment of Peripheral Intracranial Aneurysms - Andreou, A.; Ioannidis, I.; Mitsos, A. (American Journal of Neuroradiology, 2007)
BACKGROUND AND PURPOSE: Distally located cerebral aneurysms are difficult to treat with preservation of the parent vessel. We report the angiographic results and clinical outcome for 27 patients with peripheral cerebral aneurysms.METHODS: From January 2000 to June 2005, 27 patients, 13 female and 14 male, presented to our institution with peripheral intracranial aneurysms and were treated endovascularly. None of these aneurysms were mycotic in origin. The age of our patients ranged from 23 to 76 years with a mean age of 53. Twenty of the 27 patients had subarachnoid and/or intracerebral hemorrhage upon presentation. In 5 patients, the aneurysm was an incidental finding. One patient with a fusiform P2 aneurysm presented with cranial nerve III palsy, and another patient with P4 aneurysm had visual disturbances. Locations of the aneurysms were as follows: posterior cerebral artery in 9 patients, superior cerebellar artery in 5 patients, anterior inferior cerebellar artery in 1 patient, posterior inferior cerebellar artery in 5 patients, middle cerebral artery (MCA) in 5 patients, and anterior cerebral artery in 2 patients.RESULTS: Seven patients were treated with selective embolization with Guglielmi detachable coils (GDCs). Nineteen patients with fusiform aneurysms underwent parent artery occlusion (PAO). Fifteen PAOs were performed with coils and 4 with glue. One patient with a MCA aneurysm was found at the time of planned embolization to have spontaneously thrombosed the aneurysm and the distal branch of the MCA, 1 day after the initial diagnostic angiogram. Five patients (5/18 or 27.7%) who underwent PAO developed neurologic deficits. Two patients (2/18 or 11.1%) had permanent neurologic deficits (a visual field defect).CONCLUSION: Our results support that distally located aneurysms can be treated with endovascular PAO in the cases in which selective occlusion of the aneurysmal sac with GDC or surgical clipping cannot be achieved.